PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KLINIK KECANTIKAN NANISA BEAUTY & DENTAL CLINIC DI SIDOARJO - BUNGA ASRI, WIJI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Development era the increasingly this modern, beauty business keeps growing in society. This brings into competition very tight among clinic beauty to each other. Nanisa Beauty & Dental Clinic by using 6 variable services marketing mix consisting of product, price, promotion people, physical evidence, the process is expected to compete its competition. This research serves to know influence product, price, promotion people, physical evidence and process of the decision purchase products at Nanisa Beauty & Dental Clinic in sidoarjo. This research is decriptive quantitative. In this research, which is used as the population is a member Nanisa beauty & Dental Clinic in the road Taman Pinang Indah BB 1/12 Sidoarjo totalling 637 members and sample as many as 245 respondents, by using purposive sampling. From multiple linear regression analysis of the data has the value of the coefficient of determination (Adjusted R Square) of 0,507 which means the service marketing mix influence the decision purchase of 50,7%, while the remaining 49,3% is affected by other variable. Furthermore, hypothesis testing is using the t-test and F-test where Fcount at 40,789 with a significance value of 0,000 is smaller than the significance level α=0.05. Then the hypothesis is accepted, it is evident that there was significant influence between the marketing mix variable services that consist of products (X1), price (X2), promotion (X3), people (X4), physical evidence (X5), process (X6) of the decision purchase (Y). While based on the t test, the most dominant influence on purchasing decisions is price with regression coefficient values most of 0,219 compared to the other independent variables. Keyword : Service Marketing Mix, Purchase Decision